Counterpoint: Parallel Programming Wall and Multicore Software Spiral: Denial Hence Crisis. - Vishkin, Uzi (Communications of the ACM, 2022)
The author argues that computational models do not need to change to adjust for cost and technological change. He claims that random access machine, or model (RAM) is the best for algorithms and data structures, discusses the software spiral (SWS) for single central processing units (CPUs), and notes that cost-effective programming is critical for performance programming.